2016
DOI: 10.1177/0892705716662514
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of void formation in thermoplastic composites during resistance welding

Abstract: The process induced voids during resistance welding of glass fabric reinforced polyetherimide was investigated. The mechanisms of void formation in adherends, in particular the residual volatile induced voids and the fibre de-compaction induced voids, were analyzed. Due to the non-uniform temperature and stress distributions in the joints during welding, a non-uniform void distribution was observed in the joints, with more voids generated in the middle of the joints than at the edges. Welding temperature and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…This sequential behavior can be explained by the combination of two different mechanisms [4] of deconsolidation and void generation. First, prior to melting, the moisture content in the polymer induces vapor voids.…”
Section: W Welding T Elding Tool Oolmentioning
confidence: 99%
“…This sequential behavior can be explained by the combination of two different mechanisms [4] of deconsolidation and void generation. First, prior to melting, the moisture content in the polymer induces vapor voids.…”
Section: W Welding T Elding Tool Oolmentioning
confidence: 99%
“…Prolonged or over heating leads to polymer degradation and promotes undesirable fiber motions due to excessive melting, whereas too much clamping pressure cause expulsion of melted polymer from the interface. On the other hand, increasing the applied pressure minimizes the process induced voids, mainly those caused by fiber de-compaction [ 156 ]. Nevertheless, experimental results obtained by Howie et al [ 99 ] showed an inverse relationship between the lap shear strength and the bondline thickness, which is significantly affected by the applied pressure.…”
Section: Tpc Joining and Repair Techniquesmentioning
confidence: 99%
“…Prolonged or over heating leads to polymer degradation and promotes undesirable fiber motions due to excessive melting, whereas too much clamping pressure cause expulsion of melted polymer from the interface. On the other hand, increasing the applied pressure minimizes the process induced voids, mainly those caused by fiber de-compaction [156].…”
Section: Resistance Heatingmentioning
confidence: 99%
“…10,11 Non-uniform heat distribution limits the size of the weld area and introduces defects in weld joints such as voids. 12 Studies have achieved higher values with PEI/CF, because the fiberglass (GF) obtains lower adhesion than the HE/matrix interface. 10,11…”
Section: Introductionmentioning
confidence: 99%